Multiple concomitant mechanisms contribute to low platelet count in patients with immune thrombocytopenia - Grodzielski, Matías (2019)
Mechanisms leading to low platelet count in immune thrombocytopenia (ITP) involves both decreased production and increased destruction of platelet. However, the contribution of these pathologic mechanisms to clinical outcome of individual patients is uncertain. Here we evaluated diferent pathogenic mechanisms including in vitro megakaryopoiesis, platelet/megakaryocyte (MK) desialylation and MK apoptosis, and compared these efects with thrombopoyesis and platelet apoptosis in the same cohort of ITP patients. Normal umbilical cord blood-CD34+ cells, mature MK derived cells or platelets were incubated with plasma from ITP patients. Despite inhibition of thrombopoiesis previously observed, megakaryopoiesis was normal or even increased. Plasma from ITP patients afected the sialylation pattern of control platelets and this efect occurred concomitantly with apoptosis in 35% ITP samples. However, none of these abnormalities were observed in control MKs incubated with ITP plasma. Addition of mononuclear cells as immune efectors did not lead to phosphatidylserine exposure in MK, ruling out an antibody-mediated cytotoxic efect. These results suggest that both desialylation and apoptosis may be relevant mechanisms leading to platelet destruction although, they do not interfere with MK function. Analysis of these thrombocytopenic factors in individual patients showed no specifc distribution pattern. However, the presence of circulating antiplatelet autoantibodies was associated with higher incidence of abnormalities. In conclusion, the causes of thrombocytopenia are multifactorial and may occur together, providing a rational basis for the use of combination therapies targeting concomitant ITP mechanisms in patients with refractory disease.